Management Strategy Mangrove Ecosystem Base On Multy Criteria Decision Making Analysis (Case In Bunaken Island, Manado City, Indonesia) - Joshian Nicolas William Schaduw (Sam Ratulangi University, 2020)
This research purpose is to analyze the effectiveness of mangrove ecosystem management strategy in Bunaken Island of Bunaken National Park in Manado City, North Sulawesi Province. The research used the research methods of field surveys, sampling, and literature studies for several components that require periodic data. The data analysis used in this research is the Criteria Decision Making Analysis (MCDMA) with the Rapid Appraisal of Mangrove Ecosystem Sustainability (RAPMECS) tools modified from the Rapid Appraisal for Fisheries (RAPFISH). The obtained data will analyze the effectiveness of the ecological, socio-economic, and institutional dimensions that directly affect the mangrove ecosystems. It is indicated that the mangrove ecosystem management sustainability dimension in Bunaken Island is poor, and the socio-economic and institutional dimensions are not good. The main point that makes the management sustainability dimension unfavorable is the island slope and total extent of the mangrove ecosystem area. As the buffer zone, the mangrove ecosystem is low effective, this island is vulnerable to sea currents and waves. The strategies to minimize the vulnerability of this island from sea currents and waves include the increase of the mangrove ecosystem area, community awareness and participation in managing the mangrove ecosystems, and the supporting infrastructure in the mangrove ecosystem management activities.Keywords: Strategy; Management; Mangrove; BunakenABSTRAKKajian ini bertujuan untuk menganalisa efektivitas strategi pengelolaan ekosistem mangrove Pulau Bunken, yang masuk dalam kawasan Taman Nasioanl Bunaken di Kota Manado Provinsi Sulawesi Utara. Kajian ini menggunakan metode penelitian antara lainÂ survei lapangan, sampling, dan studi literatur pada beberapa kompenen yang membutuhkan data berkala. Analisis data bersifat Multy Criteria Decision Making Analysis (MCDMA) dengan tools Rapid Apraisal of mangrove ecosystem sustainability (RAPMECS) yang dimodifikasi dari the Rapid Appraisal for Fisheries (RAPFISH). Data yang didapatkan untuk menganalisa efektivitas dimensi ekologi, sosial-ekonomi, dan kelembagaan yang mempengaruhi ekosistem mangrove. Pada dimensi ekologi terindikasi keberlanjutan pengelolaan ekosistem mangrove di Pulau Bunaken kurang baik, sedangkan pada dimensi sosial ekonomi dan kelembagaan kurang baik. Hal utama yang membuat keberlanjutan pengelolaan pada dimensi ekologi kurang baik adalah kemiringan lereng pulau dan luasan dari ekosistem mangrove. Akibat dari rendahnya efektifitas mangrove sebagai buffer zone membuat pulau ini rentan terhadap aksi laut yaitu arus dan gelombang. Strategi yang dapat dilakukan meminimalkan kerentanan pulau ini antara lain adalah penambahan luasan ekosistem mangrove, peningkatan kesadaran dan partisipatifÂ masyarakat dalam pengelolaan ekosistem mangrove, dan peningkatan infrastruktur pendukung dalam kegiatan pengelolaan ekosistem mangrove.Kata Kunci: Strategi; Pengelolaan; Â Mangrove; Bunakensupporting infrastructure in the mangrove ecosystem management activities.